Plan de negocios de la empresa Verdulight dedicada a la comercialización de hortalizas orgánicas en el municipio de Villamaria - Caldas (2013)
The present work intends to implement a business plan in VERDULIGHT Company dedicated to the marketing of organic vegetables at the town of VILLAMARIA, Caldas, in order to contribute to the health of consumers given that this kind of vegetables have not been subjected to the application of products such as fertilizers, herbicides or pesticides coming from chemical type. Similarly, the soil in which these products are grown is irrigated either with any of these chemicals. One of the symptoms found in this study, is the fact that producers planted more vegetables increasingly using agrochemicals, motivated in part by the lack of incentives and training for organic crop production, the result is necessarily a product contaminated with agrochemicals, therefore, implementing the marketing of organic products and the use of organic fertilizers on their crops, will ensure that consumers improve their eating habits that contribute to the improvement of their health. As such, it will create an organic vegetable marketer considering market conditions, legal, administrative and financial. Once analyzed the potential market to commercialize the product customer requirements, marketing strategies have been proposed during this work are presented and are aimed at achieving competitive advantage. To be clear about their duties and functions, are described each job and within economic analysis determined the initial investment for the project, its costs, and income. Finally is the study of financial feasibility that allowed meeting investment make, revenues and expenditures projected five years, income statements, feasibility indicators as VPN and other indicators analyzed.